Industrial Talk Data Warehouse Practice on Cloud and on Premise - Nor Azuana, Ramli (Pusat Sains Matematik UMPSA, 2023)
Centre for Mathematical Sciences (CMS) UMP has organised the Data Analytic Industrial Talk on 16th June 2023 through Microsoft Team Online Platform. This industrial talk program was held in conjunction with a session with an industrial lecturer for Data Warehousing and Data Wrangling courses.